MTHFD1L-Mediated Redox Homeostasis Promotes Tumor Progression in Tongue Squamous Cell Carcinoma - Li, Hao; Fu, Xiaoyan; Yao, Fan; Tian, Tian; Wang, Chunyang; Yang, Ankui (Frontiers in Oncology, 2019)
Background: Routine changes in cell metabolism can drive tumor development, as the cellular program develops to promote glycolysis and redox homeostasis during tumor progression; however, the associated mechanisms in tongue squamous cell carcinoma (TSCC) remain unclear. Methods: We investigated methylenetetrahydrofolate dehydrogenase 1–like (MTHFD1L) expression, its clinical relevance, redox modification, and molecular mechanisms using TSCC cells and tissues. The antitumor effects of MTHFD1L knockdown on TSCC tumorigenesis were evaluated in vitro and in vivo. Kaplan-Meier curves and the log-rank test were used to analyze disease-free survival and overall survival. Results: TSCC patients with high expression levels of MTHFD1L had shorter overall survival (P<0.05) and disease-free survival (P<0.05). Knockdown of MTHFD1L reduced nicotinamide adenine dinucleotide phosphate (NADPH) levels and increased reactive oxygen species (ROS), which accelerated cell death under oxidative stress, such as hypoxia or glucose deprivation. Additionally, inhibition of MTHFD1L suppressed TSCC cell growth and delayed the cell cycle, including in xenograft experiments. Conclusions: MTHFD1L confers redox homeostasis and promotes TSCC cell growth, which provides a great opportunity to study tumor metabolism in head and neck cancer. The mTORC1–4EBP1–eIF4E axis may affect the expression of MTHFD1L in TSCC. Inhibition of the expression of MTHFD1L may be an actionable and effective therapeutic target in TSCC.